siRNA a promising tool for diabetes complications - Moqbel Ali Moqbel Redhwan; Hariprasad M．G; Suman Samaddar; Sumaia Abdulbari Ahmed Ali Hard (Elsevier, 2023)
RNA interference (RNAi) is a naturally occurring process of gene regulation that has been harnessed to silence specific genes in various cell types, including those involved in diabetes complications. Small interfering RNA (siRNA) is an RNA molecule that activates RNAi and targets specific genes for degradation. Recent research has demonstrated that siRNA holds promise as a tool for treating diabetes complications, including diabetic neuropathy, retinopathy, and nephropathy. In preclinical studies, siRNA has been shown to effectively target genes involved in these complications, resulting in improved clinical outcomes. One potential advantage of siRNA therapy is its ability to selectively target specific genes without disrupting endogenous mRNA pathways, which reduces the risk of off-target effects. Additionally, siRNA has the potential to provide long-lasting effects with a single dose, which could result in reduced treatment frequency and improved patient compliance. While promising preclinical results have been, several challenges still need to be addressed before siRNA can be used in clinical practice. These include delivery issues, as siRNA molecules rapidly degrade in the bloodstream and cannot cross cell membranes without assistance. Despite these challenges, the potential of siRNA as a tool for treating diabetes complications is exciting, and further research is needed to determine its safety and efficacy in clinical trials. With continued investigation and refinement, siRNA has the potential to become an important therapeutic tool for the treatment of diabetes complications, improving patient outcomes and quality of life.